POLICY OF THE KINGDOM OF SERBS, CROATS AND SLOVENES / YUGOSLAVIA ON THE MIGRATION MOVEMENTS OF THE TURKISH AND MUSLIM POPULATION FROM THE VARDAR PART OF MACEDONIA 1918-1941 (Annual of the Faculty of Philosophy in Skopje, 2009)
The military defeats and the retreat of the Ottoman Empire from the Balkan countries, in the XIX and in the beginning of the XX century, were the reason for significant ethnical and demographic changes of the Balkans. The emigration of the Turkish and Muslim population from Macedonia after the Balkan Wars was only a continuation of a longer process, which previously was carried out in the neighboring countries. Like the Turks, a part of the Macedonians - Muslims and the Albanians also migrated from the Vardar part of Macedonia. After the creation of the Kingdom of Serbs, Croats and Slovenes / Yugoslavia, the Yugoslav governments, especially in the 30s, following the example of the Greece, Bulgaria and Romania, sought to conclude a treaty with Turkey for organized migration of the part of the Turks, but also other Muslims, above all Albanians. In 1938 the Yugoslav and the Turkish government signed a Convention on migration of 40.000 Turkish and Muslim families from the territory of Yugoslavia, i.e. from Macedonia and Kosovo. As a result of the domestic resistances, the foreign pressure and the beginning of the World War II, this Convention was not ratified by the both countries.
Keywords: BALKAN WARS; MIGRATIONS; TURKS; MUSLIM POPULATION; CONVENTION ON MIGRATION; TURKEY; KINGDOM OF SERBS, CROATS AND SLOVENES / YUGOSLAVIA